2009
DOI: 10.2214/ajr.08.1223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indirect Isotropic MR Arthrography and Conventional MR Arthrography of Labral Lesions and Rotator Cuff Tears: A Prospective Study

Abstract: Three-dimensional isotropic MR arthrography sequences with multiplanar reconstruction can provide a similar capability for the diagnosis of labral and rotator cuff lesions as conventional MR arthrography sequences but in a shorter imaging time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 23 publications
1
54
2
2
Order By: Relevance
“…Nonetheless, more recent studies have started using much higher field strength machines to image the glenoid labrum. Four studies assessed MRA using a 3.0 T machine [16,17,28,29], while two MRI studies were performed using 3.0 T procedures [29,30]. When these papers were specifically reviewed, the MRI findings indicated greater diagnostic test accuracy for the higher field strength imaging compared to our meta-analysis results.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Nonetheless, more recent studies have started using much higher field strength machines to image the glenoid labrum. Four studies assessed MRA using a 3.0 T machine [16,17,28,29], while two MRI studies were performed using 3.0 T procedures [29,30]. When these papers were specifically reviewed, the MRI findings indicated greater diagnostic test accuracy for the higher field strength imaging compared to our meta-analysis results.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to this, technical advances with the advent of 3.0 T MRI systems have provided increased signal-to-noise ratio to achieve faster images to reduce the indicated of motion artefacts and higher resolution images to increase the detection of gleniod injuries [17,27]. The effect of magnetic resonance field strength was not formally assessed in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 15 min of exercise following intravenous gadolinium injection prior to MRI, increases signal intensity in the joint and improves the sensitivity in the detection of shoulder pathology [20, 21]. A study by Oh et al, encompassing 36 patients, reported a lower specificity and sensitivity in the detection of superior labral tears, but better results in detection of anterior labral tears by I-MRA [22]. …”
Section: Discussionmentioning
confidence: 99%
“…While Yagci et al [4] analyzed the efficacy of indirect MR arthrography and noncontrast MRI for suspected rotator cuff abnormalities, the study was based on a small number of patients, without statistical comparison between the two techniques (except for the interobserver agreement). Previous studies have revealed that indirect MR arthrography is highly accurate in diagnosing overall and full-thickness tears of SSP-ISP tendons [4,9,[12][13][14]24]. In contrast, the correct diagnoses of a partial-thickness tear remains difficult despite the use of intravenous contrast media [12,14,24].…”
Section: Discussionmentioning
confidence: 99%